Synopsis of the genus Galactia (Phaseoleae, Papilionoideae, Leguminosae) in Brazil - Ceolin, Guilherme B.; Miotto, Sílvia T. S. (Phytotaxa, 2013)
A synopsis of the genus Galactia (Leguminosae) in Brazil, including taxonomy, ecology, economic potential, and conservation is presented. A taxonomic key, description of one new species (Galactia cordifolia), new synonyms, illustrations, a brief description of the main diagnostic characters of each species, and notes on distribution, ecology and uses are presented.